Global trends in extension provision, staffing, and methods - Davis, Kristin E.; Alex, Gary (International Food Policy Research Institute, 2020)
This chapter is a landscape view of extension globally. It compares the recent status to the situation several decades ago, when earlier global assessments were conducted. In particular, we look at best-fit characteristics, including legal status and governance of extension providers, staffing, and advisory methods and clientele. We also look at trends and recent developments using the global assessments and recent literature. There have been several major efforts to collect worldwide extension data. Surveys were conducted in 1975 and 1980 by the University of Illinois (Swanson and Rassi 1981). Follow-up work was conducted by the Food and Agriculture Organization (FAO) in 1988–1989, and by the International Food Policy Research Institute (IFPRI) and Global Forum for Rural Advisory Services (GFRAS) in 2009–2012. However, there were never any narrative reports produced or much analysis conducted of this data collection effort. Swanson and Rassi (1981) and FAO (1991) were simply directories. GFRAS (2012) is a database; the only report produced was Swanson and Davis (2014), which was a 14-page document giving some key details on the status of extension by region and with a table providing numbers of agents.